Leaps of faith : An international arts project for the Green Line and the city of Nicosia, Cyprus. - Gregos, Katerina; Kosova, Erden; Nassari, John; Hadjipavlou, Maria; Yasin, Nese; Nicosia (Istanbul : Kolektif, 2005)
Zaatari, Akram ; Rainio, Minna ; Roberts, Mark ; Blazevic, Damir ; Dinko, Peracic ; Veljacic, Miranda ; Silovic, Ana ; Sancanin, Marco ; Philipsz, Susan ; Perjovschi, Dan ; Panayiotis, Michael ; Landau, Sigalit ; et al.
Nicosia, 13-29 May, 2005
kunstcatalogus